Study on dynamic performance of wind power planetary gears with flexible pins - LIN Xu; DAI Peng (Jixie chuandong)
ObjectiveIn the planetary gear system, the presence of the flexible pin shaft makes the nonlinear behavior in the gear transmission process more complex. To reveal the nonlinear dynamic behavior of the planetary gears in the wind power gearbox with flexible pins, a translational torsional coupling dynamic model and motion differential equations of the gear train were established.MethodsKey factors such as the stiffness of the flexible pin, backlash, time-varying meshing stiffness, and error excitation were considered comprehensively. The influence of pin stiffness on the nonlinear dynamic performance of planetary gear was investigated by studying the dynamic meshing force, phase diagram, acceleration, Poincare diagram, and axis trajectory of sun gear and planetary gears.ResultsThe results show that as the stiffness of the flexible pin decreases, the vibration acceleration and dynamic meshing force fluctuation range of the sun and planetary gears decrease and then increase. The motion of the sun gear and planetary gear transforms from periodic to quasi periodic when the stiffness of the flexible pin decreases. The stiffness of the flexible pin has a smaller impact on the floating range of the sun gear but a larger impact on the floating range of the planetary gear. The floating trajectory range of the planetary gear is greatly increased by reducing the stiffness of the pin shaft.